The Influence of the July 2024 Revolution on the Mental Health of Tertiary Level Students in Bangladesh - Md.Fajlay Rabbi; S.M.Shamsul Alam; Mihir Halder (Indonesian Journal on Education (IJoEd), 2025)
The July 2024 Revolution in Bangladesh marked a critical political shift, resulting in the removal of a fascist regime. While this movement was hailed as a victory for democracy, its psychological toll on tertiary-level students-many of whom actively participated in protests or witnessed state repression-remains underexplored. This study investigates the mental health impact of the revolution, focusing on stress, trauma, and post-revolution anxiety among university students. A mixed-method approach was employed, combining quantitative surveys (N = 500 students) and qualitative in-depth interviews (N = 30 students) from major universities across Bangladesh. The Depression, Anxiety, and Stress Scale (DASS-21) and Post-Traumatic Stress Disorder Checklist (PCL-5) were used to assess mental health outcomes. Additionally, thematic analysis was conducted on interview data to identify key stressors and coping mechanisms. Findings reveal that 67% of students reported moderate to severe anxiety, 42% displayed PTSD symptoms, and 48% experienced depression. Key stressors included fear of government surveillance (59%), political disillusionment (46%), and academic uncertainty (72%). Qualitative analysis highlighted themes of political trauma, social fragmentation, and empowerment through activism. These results suggest that while the revolution fostered a sense of civic engagement, it also exacerbated mental health distress and long-term socio-political anxiety. The study underscores the need for institutional mental health interventions, academic recovery programs, and policy initiatives to mitigate the psychological consequences of political upheaval among students.